El sistema de abastecimiento hidráulico de la Almunia de los Alijares. Estado de la cuestión - García Pulido, Luis José (En la España Medieval, 2007)
The extraction of gold deposits from the Hill of the Sun (Cerro del Sol) using hydraulic mining techniques could go back to the end of the 2nd century B.C. Much later, in the last quarter of 14th century, the Nasrid monarch Mu™ammad V, one of the builders of the Alhambra, decided to locate the Palace of the Alijares well above the limit line marked by the Royal Channel (Acequia Real). The relationship between the Roman hydraulic system on the Hill of the Sun and others developed in Islamic times could contain the keys to an historical problem that has not been solved: explaining the system of water supply to this royal palace.